Next Generation Copper Mediators for the Efficient Production of 18F‐Labeled Aromatics. Issue 2 (17th November 2022) - Hoffmann, Chris; Kolks, Niklas; Smets, Daniel; Haseloer, Alexander; Gröner, Benedikt; Urusova, Elizaveta A.; Endepols, Heike; Neumaier, Felix; Ruschewitz, Uwe; Klein, Axel; Neumaier, Bernd; Zlatopolskiy, Boris D.
Abstract: Cu‐mediated radiofluorination is a versatile tool for the preparation of 18 F‐labeled (hetero)aromatics. In this work, we systematically evaluated a series of complexes and identified several generally applicable mediators for highly efficient radiofluorination of aryl boronic and stannyl substrates. Utilization of these mediators in n BuOH/DMI or DMI significantly improved 18 F‐labeling yields despite use of lower precursor amounts. Impressively, application of 2.5 μmol aryl boronic acids was sufficient to achieve 18 F‐labeling yields of up to 75 %. The practicality of the novel mediators was demonstrated by efficient production of five PET‐tracers and transfer of the method to an automated radiosynthesis module. In addition, ( S )‐3‐[ 18 F]FPhe and 6‐[ 18 F]FDOPA were prepared in activity yields of 23±1 % and 30±3 % using only 2.5 μmol of the corresponding boronic acid or trimethylstannyl precursor. Abstract : Evaluation of a series of Cu(II) complexes revealed several highly efficient mediators for radiofluorination of aryl boronic and stannyl substrates. After optimization of the reaction conditions, their application enabled preparation of seven PET‐tracers in improved radiochemical yields and/or using significantly lower precursor loadings.